KETERLAMBATAN BARANG PESANAN IMPOR BERDASARKAN PERATURAN MENTERI PERDAGANGAN NOMOR 82 TAHUN 2016 TENTANG KETENTUAN IMPOR BESI ATAU BAJA, BAJA PADUAN DAN PRODUK TURUNANNYA DI PT. TRAKINDO UTAMA SAMARINDA - Arifin, Muhammad Bustanil (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTThe purpose of the study to determine the impact and which become an obstacle in the booking Imported goods include Iron or Steel, Alloy Steel and its Derivatives on the issuance of Minister of Trade Regulation Number 82 Year 2016 in the PT. Trakindo Utama Samarinda.There are some things impact and become an obstacle in the booking Imported goods include Iron or Steel, Alloy Steel and its Derivatives on the issuance of Minister of Trade Regulation Number 82 Year 2016 in the PT. Trakindo Utama which is as follows: a long time needed to confirm the Surveyors need in the Verification which are not listed in regulations and which amount is not determined by considering the base benefits, contrary to the objective of Minister of Trade Regulation Number 82 Year 2016, namely, that to encourage the improvement of national competitiveness, the need to perform the simplification of licensing in the field of trade,Â  in particular the imports of iron or steel, alloy steel, and its derivatives. The impact Decreased performance and the credibility of related to the willingness of the spare parts category iron Steel in PT. Trakindo Utama Samarinda or PT. Trakindo Utama Indonesia as the dealer Caterpillar Indonesia started to become a material consideration relevant government and in the business world.Â Keywords : PT. Trakindo Utama, Regulation of the Minister of Trade Number 82 of 2016 concerning Provisions on the Import of Iron or Steel, Alloy Steel, and its Derivative Products.